Monitoring the imidization reaction of polyimide thin films using an in-situ LIBS approach - Birgit Achleitner; Tobias Huber; Silvia Larisegger; Michael Nelhiebel; Patrick Knaack; Andreas Limbeck (Polymer Testing)
High-performance polymers like polyimides are well known for their outstanding chemical and physical properties and play an important role in high-demanding applications like automotive, aerospace, medical, etc. Polyimide thin films are especially useful in the electronics industry to protect the underlying devices from elevated temperatures, humidity, corrosive gases and high voltages. Therefore, the curing of polyimides has been studied extensively to ensure ideal material properties and new tools and methods for sample characterization are of great interest. Besides conventional techniques like Fourier Transform Infrared Spectroscopy (FT-IR), Thermogravimetric Analysis (TGA) or Differential Scanning Calorimetry (DSC), Laser Induced Breakdown Spectroscopy (LIBS) has been introduced recently to monitor the imidization reaction of a polyimide thin film. To obtain information about the temporal evolution of the reaction as well as optimize labor- and time-consuming sample preparation, a heating chamber for simultaneous thermal treatment and LIBS measurements (in-situ experiments) was developed and successfully used for imidization studies of self-synthesized polyimides. Besides a general introduction of the chamber design, the results of the in-situ investigation are presented: isothermal studies to gain temporal information about the imidization reaction of a single film and stepwise heating to investigate the influence of the curing temperature. Finally, LIBS depth-profiling revealed depth-resolved information about the imidization degree over the entire film thickness, illustrating one of the great advantages of the LIBS technique.